Folk History or History in Folklore−New Subsidiary Historic Discipline (Global Journal of Human-Social Science, 2019)
The object of research is Russian folklore in various historic periods The subject of research is the historic content in folklore words phrazes texts and Russian traditional forms of material culture In the historic content of Russian traditional culture the author distinguishes between historic events and accompanying historic moods that may not coincide in meaning and essence Special attention is paid to the fact how folklore narrations influenced the quality of the Russian language The Russian folklore language is presented as historic indicator What is the reason for appearance of rich folklore forms and primitive simplified in stylistic esthetics forms The author sets the problem how does folklore tradition based on historic context sort out the best examples of folklore A comparative method of research is used various folklore examples and forms of Russian traditional culture were compared for matching culture standards of linguistic communication the more rough the historic process is the lower esthetics and ethics of folklore communication is produced
Keywords: russian history; russian traditional culture; folklore; narrations; academic research; subsidiary